PANDANGAN HUKUM ISLAM TERKAIT DAMPAK NEGATIF DUNIA MAYA TERHADAP KASUS GUGATAN PERCERAIAN DI PENGADILAN AGAMA KOTA JEMBER - Jufa'i Reflisayah, Muhammad Aqsa; Muhtadin, Sabilul (ZONAsi: Jurnal Sistem Informasi, 2024)
Cyberspace has various positive and negative influences on human life, including its influence on the continuity of a marriage or household, where one of the consequences is divorce from a household. Divorce cases are complex issues in Islamic family law, involving clear legal procedures as well as emotional, social and economic aspects. In this context, virtual media can be a significant factor in shaping public perceptions of divorce cases. This research analyzes cyber media activities in the causes of divorce lawsuits that occurred in the Jember religious courts, classifies the cyber activities that are the causes of divorce lawsuits and describes the number and cases that occurred during January to April 2024 in the Jember Religious Courts. The type of method in this research is included in the type of library research. The results of the data analysis show that there were 2048 decisions, of which, from this data, the data on divorce decisions at the Jember religious court was in the form of 1,495 divorce cases, and of these 1,495 cases, 108 cases were caused by virtual media activity, a percentage reaching 7%. The biggest cause of divorce lawsuits caused by the virtual world is in the Social Media group, where of the 108 cases of divorce lawsuits, there are 89 cases of divorce lawsuits caused by Social Media and followed by Online Gambling and Games as the cause of divorce lawsuits. There were 19 cases of lawsuits. There was 1 case of lawsuit caused by online gambling and games where the perpetrator was a woman. In the perfection or guidance of Islamic law, there are many verses of the Koran and Hadith which regulate and become signs in activities in the virtual world, including: Surah Al-Isra Verse 32, Surah An-Nur Verses 30-31, Surah Al -Ahzab Verse 35, Surah An-Nisa Verse 34, Surah An-Nisa Verse 35, Surah Al-Baqarah Verse 231, Surah Al-Hujurat Verse 12, Surah At-tahrim Verse 6, Surah Al-Ma'idah Verses 90-91 , Surah Al-Baqarah Verse 219 and Hadith about Maintaining Honor (HR. Bukhari and Muslim), Hadith about the husband's responsibility as a leader (HR. Bukhari and Muslim), Hadith about saying good things or remaining silent (HR. Bukhari and Muslim), Hadith about abandoning what is not useful (HR. Tirmidhi), Hadith about the Prohibition of Gambling (HR. Muslim). Based on Islamic Perspective or Law, the principles that must be applied in cyber activities to prevent conflict and divorce, Maqasid Al-Shariah (Sharia Goals), Hisbah (Supervision) and Maslahah (Prosperity).